Media Siber Dalam Tinjauan Semiotika Charles Sanders Peirce - Mirza Azkia Muhammad Adiba (Al-Maquro' : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Cyber media has become a prima donna for people in the current era, both from small children who still have no relationship to the elderly, in its use it is often beyond the ability of someone who has lost their real life and life in cyberspace, in this paper explaining this through Charles Sanders Peirce's semiotic approach, is expected to be able to reveal the meaning of symbols, signs found on cyber media. The results of this paper show that everything contained in cyber media is a form of capitalism that forces users to become consumptive people through signs and symbols on cyber media. Applications that utilize the internet in general also create a virtual world that is simulacra in society.